Community Economic Development Strategic Planning for Rural Communities: A Case Study of Successful Programs - John Preissing (Adult Education Research Conference, 2006)
This is an empirical case study which examines the extent to which extension-led community economic development strategic planning (CEDSP) programs in rural communities have been effective and why.
Keywords: Developmental planning; rural communities; economic development